RANCANG BANGUN ALAT PENGHITUNG PENGUNJUNG PERPUSTAKAAN DENGAN MICROCONTROLER AT89S51 DENGAN PENAMPIL LCD - - Paring; Bambang Supradono; Aris Kiswanto (MEDIA ELEKTRIKA, 2011)
Library is the heart of campus life and the entry gate of science. The number of visitors to the library is an indicator of the quality of the academic atmosphere in the university. Visitors during this data collection is done manually have limitations in terms of data accuracy and data processing electronics to follow up.Data has advantages in data accuracy and process. In this research aims to design tool Counters Visitors to the library with AT89S51 Microcontroller with LCD Viewer. This tool will automatically calculate how many students get in the library. So by knowing the number of student activities at the college library will be easy to determine the next steps to improve the quality of services at the library.Keywords : Libraries, electronic data, microcontroller AT89S51